PENGARUH KECERDASAN EMOSIONAL, PERILAKU BELAJAR, EFIKASI DIRI DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Milla, Zahrotul; Putra Prima, Argo (SCIENTIA JOURNAL, 2024)
Educational development plays an important role and is a measure of the progress or decline of a country'sdevelopment process. Education is the beginning of the formation of behavior, thoughts and character of everyhuman being. University is the highest achievement in Indonesia's national education system. Having highereducation can produce talented individuals who can better shape the future of a country. This research aimsto determine the influence of emotional intelligence, learning behavior, self-efficacy and interest in learning onthe level of understanding of accounting. Researchers conducted research at several universities in BatamCity using quantitative-based research and with a sample size of 300 respondents. And it results that emotionalintelligence, learning behavior and interest in learning have a positive and significant effect, while self-efficacydoes not have a significant effect on the level of understanding of accounting.